Alternative protein and microbial food production with Yarrowia lipolytica: precision, biomass and traditional fermentation strategies - Lu,M; Hapeta,P; Ledesma-Amaro,R (Trends in Food Science & Technology, 2025)
BackgroundWith the rapid growth of the global population, humanity is expected to face significant challenges by 2050, such as food crises, resource shortages, and climate change. The emergence of cellular agriculture not only offers promising solutions to these issues and enhances animal welfare but also provides a sustainable, healthy, and safe approach for the development of future food systems. Precision fermentation, which utilizes microorganisms as cellular factories to produce high-value functional products, plays a pivotal role in the field of cellular agriculture. Additionally, with the increasing demand for high-quality protein-containing food, identifying alternative food sources is essential. Production of alternative proteins via fermentation results in the smallest carbon footprint and generates more stable products, attracting significant interest from both academia and the food industry.Scope and approachThis review discusses the production of alternative proteins in Yarrowia lipolytica via fermentation. It addresses the advantages of using Y. lipolytica as a protein production platform, improvements in production through fermentation strategies, examples of expressed proteins from literature and patents, and the current regulatory aspects and social considerations.Key findings and conclusionsY. lipolytica have a safe usage status, a capacity to utilize various feedstocks, and unique advantages in protein production. Through precision fermentation, specific proteins can be produced, and at scale production can be achieved with appropriate parameter optimization. Additionally, Y. lipolytica is expected to play a critical role in the field of food fermentation due to its rich nutritional profile and desirable organoleptic properties. It not only provides a valuable source of alternative proteins but also improves food flavours, enriches nutritional value, and facilitates the development of new functional foods, thus broadening the scope for future food